Menginduksikan Nilai-Nilai Budaya Tanjung Jabung Timur dalam Proses Konseling - Affan Yusra; Randy Aryanto (Journal on Education, 2023)
Culture consists of knowledge, beliefs, arts, morals, laws, customs, and habits practiced by a particular society. Culture also encompasses everything acquired or learned by humans as part of a community, thus becoming cultural values that need to be preserved, upheld, and preserved. One example is the Malay culture in Jambi. Cross-cultural counseling can refer to relationships involving participants from different cultures or relationships involving counselors and clients who are racially and ethnically different but culturally different. Therefore, relationships, giving and receiving, or culture influence something and events. The purpose of this study is to explain the types of culturally based counseling that incorporate Jambi Malay cultural values into the counseling process.